Der Wasserhaushalt des Titicacasees nach neueren Messergebnissen - Kessler, Albrecht; Monheim, Felix (ERDKUNDE, 1968)
Since 1956, there have been 37 precipitation gauges in the Titicaca Basin (Peru and Bolivia). Apart from these, discharge measurements have been carried out since 1957 on the most important streams flowing into Lake Titicaca and on the Desaguadero. In addition, both authors have carried out their own observations. With the help of all these a map of annual precipitation for the 1957-1961 period was prepared and, using the water budget balance, evaporation, until now only estimated, was calculated. The picture of precipitation distribution is particularly surprising, with a pronounced maximum of 1150 mm over the northern part of Lake Titicaca, partly explicable in terms of relief (lower height of the east Cordillera between Cordillera Real and the Apolobamba cordillera). Above all, however, the nightly land wind with convergence of ground winds over the lake and higher humidity there, contribute to this maximum. The water budget of the lake was calculated for the five individual years 1957 to 1961. The moisture receipts of the lake are accounted for 58 % by precipitation and 42 % by surface inflow, the losses 2 % from discharge and 98 % (1480 mm) from evaporation. The mean annual level of the water budget components shows that evaporation has the lowest monthly variation in comparison to precipitation and inflow. In conclusion, the water budget of the Titicaca Basin is examined and a mean discharge co efficient of 0,21 calculated.